The wood between the worlds : adapted from The chronicles of Narnia by C.S. Lewis - Lewis, C. S., (Clive Staples), 1898-1963.; Maze, Deborah ([New York] : HarperCollins, 1998)
A picture book adapted from "The Chronicles of Narnia" in which Uncle Andrew uses a set of magic rings to send Polly and his nephew Digory into another world, where they meet the evil Queen Jadis.
"The story of Polly and Digory is based on the book The Magician's nephew by C.S. Lewis. The Magician's nephew is one of the seven titles in The chronicles of Narnia series written by C.S. Lewis"--T.p. verso.
"The world of Narnia.".
5.7.
5.7
K-3
Keywords: Fantasy; Fantastic fiction